2009
DOI: 10.1002/pen.21308
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior of poly(vinylidene fluoride)/montmorillonite nanocomposite

Abstract: The crystallization behavior of poly(vinylidene fluoride)/ montmorillonite (PVDF/MMT) nanocomposite was investigated by using differential scanning calorimeter (DSC), polarizing optical microscope (POM), and X-ray diffraction. The results showed that the crystallization behavior of PVDF was changed by adding MMT in PVDF matrix. The MMT layers in PVDF acted as effective nucleation agents. It is observed that the crystallization temperature of PVDF/MMT nanocomposite was higher than that of PVDF at various coolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…The effect of nanoclay on PVDF crystalline structure in films/ thin sheets has been studied by Priya and Jog [5], Shah et al [6], Yu et al [7], Umasankar Patro et al [8], Dillon et al [9], Buckley et al [10], and Pramoda et al [11] (studies 1-7). Samples were manufactured by compression moulding at 190-200°C for few minutes, microinjection into a mould having wall temperature of 95°C, and by film casting followed by compression moulding and isothermal crystallization at 145°C for 1 h. The effect of CNTs on PVDF crystalline structure in films/thin has been studied by Levi et al [12], Zhang et al [13], Wang et al [14], Manna and Nandi [15], Kim et al [16], and W. Huang et al [17] (studies [8][9][10][11][12][13].…”
Section: Nanofilled Pvdf Filmsmentioning
confidence: 96%
“…The effect of nanoclay on PVDF crystalline structure in films/ thin sheets has been studied by Priya and Jog [5], Shah et al [6], Yu et al [7], Umasankar Patro et al [8], Dillon et al [9], Buckley et al [10], and Pramoda et al [11] (studies 1-7). Samples were manufactured by compression moulding at 190-200°C for few minutes, microinjection into a mould having wall temperature of 95°C, and by film casting followed by compression moulding and isothermal crystallization at 145°C for 1 h. The effect of CNTs on PVDF crystalline structure in films/thin has been studied by Levi et al [12], Zhang et al [13], Wang et al [14], Manna and Nandi [15], Kim et al [16], and W. Huang et al [17] (studies [8][9][10][11][12][13].…”
Section: Nanofilled Pvdf Filmsmentioning
confidence: 96%
“…Wide angle X‐ray diffraction data are presented in Figure for PVDF‐HFP and PVDF‐HFP nanocomposites containing 1, 3, and 5 wt% GO. From this figure, it can be inferred that PVDF‐HFP exhibits three strong reflections at 2θ = 20.46°, 21.48°, and 23.15° corresponding to the (100), (020), and (110/200) planes of α‐phase, respectively . Moreover, the weak broad peak at 24.33° is related to β‐crystals while the one at 30.86° is due to γ crystals.…”
Section: Resultsmentioning
confidence: 99%
“…It should be observed that though the properties of polivinylidene fluoride PVDFnanoclay composites have been studied repeatedly [24][25][26][27][28][29][30] there are no information on the properties of PVDF-MCM41 nanocomposites. The interaction of the clay nanoparticles with PVDF has been found to result an increase in the rate of molecular relaxation processes both in the amorphous and in the crystalline phase of the polymer [30].…”
Section: Introductionmentioning
confidence: 95%